Meta-analysis of the effects of CYP3A5*3 gene polymorphisms on tacrolimus blood concentration and effectiveness in Chinese patients with membranous nephropathy - Dai, Xiaona; Yuan, Fang; Chai, Lan (Frontiers in Pharmacology, 2024)
Abstract Objective: To systematically evaluate the relationship between CYP3A5*3 gene polymorphisms and the blood concentration and effectiveness of tacrolimus (TAC) in patients with membranous nephropathy (MN). Methods: PubMed, Cochrane Library, Embase, Web of Science, CBM, China Knowledge Base, Wanfang, Vipshop, ReadShow, Clinical Trials Registry, and other databases were searched. Studies on the relationship between CYP3A5*3 gene polymorphism and TAC blood concentration in MN patients were collected, and meta-analysis was performed using Stata. 16 software. INPLASY registration number: INPLASY202430083. Results: A total of 8 publications were included in the study, including 498 MN patients. The CYP3A5*3 gene polymorphisms are associated with tacrolimus blood levels in patients with MN.The results of the relationship between CYP3A5*3 genotypes polymorphisms and tacrolimus blood trough concentrations of AA+AG genotype was lower than GG genotype at ≤1 month[WMD=-2.08,95%CI(-2.57,-1.59),P<0.001], 1-6 months[WMD=-0.63,95%CI(-0.98,-0.27),P<0.001],however was not statistically significant at ≥6 months (P=0.211). Furthermore, the subgroup analysis revealed that the dose-adjusted concentration of tacrolimus (C0/D) of AA+AG genotype were lower than those of GG genotype at ≤1 month [SMD=-1.93,95% CI (-2.79, -1.08), P < 0.001], 1-6 months [SMD=-2.25,95%CI (-2.71, -1.79), P < 0.001] and ≥6 months [SMD=-2.36,95%CI(-2.86,-1.86), P < 0.001]. Besides,there was no statistically significant difference in effectiveness between the two groups at 3, 6, and 12 months of TAC administration (P＞0.05). Conclusion: Serum TAC concentrations in MN patients were correlated with the CYP3A5*3 genotype polymorphism. Detection of the CYP3A5*3 genotype before the administration of TAC may provide some clinical value for optimizing the treatment of MN patients.